Analisis Kesulitan Belajar Matematika Materi Aljabar, Persamaan Linier, Perbandingan Senilai dan Tak Senilai, Bangun Datar, dan Bangun Ruang Siswa Kelas VII UPT SMPN 35 Medan - Nabila Rizki Aprilia; Ila Nazila; Miftah Kurnia Arfah Pulungan; Elsa Nandita (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to understand and analyze the mathematics learning difficulties faced by class VII students at SMPN 35 Medan. Through a qualitative descriptive approach, this research explores the factors that cause learning difficulties and provides solutions that can be implemented. The research method involves written tests and interviews with students and teachers. The results of the research reveal that students face challenges in understanding basic concepts such as algebra, linear equations, equivalent and non-equivalent comparisons, as well as plane figures and spatial figures. Internal and external factors, such as students’ cognitive abilities and less effective teaching methods, influence their mathematics performance. This research suggests a more interactive learning approach, training for teachers, collaboration between schools and parents, and regular evaluation to improve students’ mathematical understanding and performance in the future. Thus, this research makes a significant contribution to efforts to improve the quality of mathematics learning in schools.